Pengaruh Komunikasi Internal, Lingkungan Kerja Fisik, dan Beban Kerja Terhadap Kinerja Karyawan PT. Sinergi Gula Nusantara - Arisma Desi Fitriani; Indah Listyani; M. Adi Trisna Wahyudi (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
This study aims to explain and prove the hypothesis regarding the effect of internal communication, physical work environment, and workload on employee performance at PT Sinergi Gula Nusantara (PG Meritjan) Kediri City. This study uses an associative approach with a quantitative method and employs , using a saturated sampling method with a total population of 80 employees and a sample of 80 employees. The analytical techniques used include validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis, t-test (partial), F-test (simultaneous), and coefficient of determination (R²), processed using SPSS version 26. Based on the results, it shows that partially internal communication has an effect on employee performance. The physical work environment variable partially has a significant effect on employee performance with a value of Sig. 0.010 < 0.05 and tcount > ttable, namely 2.634 > 1.991. The workload variable partially has a significant effect on employee performance with a value of Sig. 0.000 < 0.05 and tcount > ttable, namely 3.580 > 1.991. The variables of internal communication, physical work environment, and workload simultaneously have a significant effect on employee performance at PT Sinergi Gula Nusantara (PG Meritjan) Kediri City. The magnitude of the influence of internal communication, physical work environment, and workload on employee performance is 25.7%, while the remaining 74.3% is influenced by other variables not examined in this study.